The culture advantage - Strode, Daniel; Strode, Daniel (New York, NY Kogan Page, 2022)
"Innovation is the key to making your business go the distance. Innovate or die they say. But where does innovation lie? The answer is in your people. Far from being the privilege of the unicorns of Silicon Valley, innovation isn't dependent on business model, structure or even budget. By harnessing your people's power through a corporate culture of innovation, you unlock business opportunities that your competition won't have access to. The Culture Advantage is a blueprint to designing, implementing and sustaining a culture that will not only celebrate innovation, but will imbue it in everything your company, and its people, do.Culture evangelist, Daniel Strode, with the help of some of the world's historically most inspiring and innovative businesses like The Walt Disney Company and The LEGO Group, as well as newer companies like Art Blocks from the Web 3.0 and blockchain space, breaks down the innovation puzzle. Through evaluating your business model; daring to chip away at it; empowering your people through technologies; psychological safety and leadership; putting constraints onto their creative efforts; and hiring and collaborating with the right types of innovators, you'll discover how to enhance your adaptability and futureproof your business"--
Keywords: Business enterprises; Industrial management; Organizational effectiveness; Creative ability in business; Success in business